Analysis of the Transformation of Cash Waqf into Productive Assets at Puspas Airlangga University - Muh. Ridho Sudianto; Muhamad Farizi (Values: Jurnal Kajian Islam Multidisiplin, 2026)
Cash waqf is one of the Islamic philanthropic instruments that has significant potential in supporting social and economic development, especially in the education sector. However, the management of cash waqf still faces challenges in optimizing and transforming it into productive assets. This study aims to analyze the implementation and effectiveness of transforming cash waqf into productive assets managed by the Center for Social Fund Management (PUSPAS) of Universitas Airlangga. This research employed a qualitative descriptive approach with a case study method. Data were collected through interviews, observations, and documentation involving institutional administrators, companions of Griya Khadijah, and beneficiaries. Data analysis techniques included data reduction, data display, and conclusion drawing, while data validity was tested using source and technique triangulation. The results indicate that the transformation of cash waqf is carried out through two management sectors, namely the real sector and the non-real sector. The real sector includes the management of Griya Khadijah Islamic boarding house, scholarships, café businesses, and laundry services, while the non-real sector is managed through Islamic financial instruments such as deposits and Islamic securities. The transformation was deemed effective based on the effectiveness indicators proposed by Richard M. Steers, which include satisfaction, productivity, efficiency, adaptability, and development. In addition, the productive waqf program has provided direct benefits to students through scholarships, living cost assistance, and character development programs. This research contributes to the development of university-based productive waqf studies by showing that the integration of waqf management in the real and non-real sectors can be a model for the transformation of sustainable cash waqf and is able to support student empowerment through educational programs, scholarships, and character building.